2021
DOI: 10.1186/s12984-021-00828-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of IMU-based gait event detection during curved walking and turning in older adults and Parkinson’s Disease patients

Abstract: Background Identification of individual gait events is essential for clinical gait analysis, because it can be used for diagnostic purposes or tracking disease progression in neurological diseases such as Parkinson’s disease. Previous research has shown that gait events can be detected from a shank-mounted inertial measurement unit (IMU), however detection performance was often evaluated only from straight-line walking. For use in daily life, the detection performance needs to be evaluated in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 46 publications
(34 reference statements)
3
31
3
Order By: Relevance
“…If this and related conditions are not diagnosed promptly, the patients are more likely to suffer further injury by falling [1,2]. Recently, human activity recognition (HAR) was introduced to monitor the motion of a subject in daily life using healthcare devices to determine measures to prevent such accidents [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this and related conditions are not diagnosed promptly, the patients are more likely to suffer further injury by falling [1,2]. Recently, human activity recognition (HAR) was introduced to monitor the motion of a subject in daily life using healthcare devices to determine measures to prevent such accidents [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Because human health problems are most often expressed as measurable behaviors [11], IMUs are more suitable for daily activity data collection than other sensors. Hence, many IMUbased HAR studies have been accomplished [3][4][5]9]. Digo's study [12] was conducted to effectively recognize the working condition by wearing only one IMU in the trunk position.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is less clear how these curved trajectories impact the accuracy of various gait detection algorithms. One recent study investigated the impact of curved walking, turning, and cognitive load on detection performance of gait events using shank-mounted IMUs [19]. Results showed that detection performance was adequate for curved walking, but there were more false events detected during turning.…”
Section: Introductionmentioning
confidence: 99%
“…An IMU utilizes three axial accelerometers, gyroscopes and geomagnetometers [ 7 ]. The validity of IMUs for gait event detection has been well established [ 9 , 10 ], while evidence is limited for movement phase detection during sports performance. IMUs have several advantages over conventional video analyses.…”
Section: Introductionmentioning
confidence: 99%